Numerical nonlinear modeling and simulations of high strength reinforced concrete beams using ANSYS - Pandimani; Ponnada, Markandeya Raju; Geddada, Yesuratnam (Journal of building pathology and rehabilitation, 2022)
This study presents a comprehensive nonlinear material modeling and simulation approach of high-strength concrete (HSC) beams using the versatile finite element (FE) analysis tool ANSYS. Three reinforced concrete (RC) beams of 102 MPa strength, comprising three various percentages of tension steel reinforcement are numerically modeled and validated against the experimentally tested beams available in the literature. The interface bond-slip mechanism between the concrete and steel reinforcements along with the tension stiffening effects between the cracks is deliberately considered in the developed FE model. The mesh-sensitivity study is implemented to determine the ideal element density which influences the nonlinear solution. The load–deflection plots predicted from FEA are corroborated with the experimental curves and the FE models can able to predict closer response with the experimental curves throughout the loading history with sufficient accuracy. Subsequently, theoretical analysis based on ACI 318-19 code is executed to verify the cracking, yielding, and ultimate moments of experimental and numerical models. The ultimate loads and deflections predicted through the FE model show a maximum discrepancy of − 11.15% and − 3.06%, respectively as compared to the experimental results. The yield and ultimate loads achieved based on the ACI code exhibit a closer prediction with the experimental data as compared to the numerical analysis. The graphical contour diagrams of the FE models provide complete and worthy information throughout the beam length. The developed FE model is a valid and reliable tool to analyze the flexural nonlinear response of high-strength RC beams and can be further utilized to explore various parametric studies.